The source of leadership : eight drivers of the high-impact leader - Traversi, David M. (New Harbinger Publications, 2007)
In this pivotal book, business leader David Traversi examines the eight drivers common to all great leaders and offers advice on how readers can cultivate these powerful predictors of success and influence in their own professional lives.